Iron Deficiency Anemia and its Relation with Junk Food - Sheherbano Yahya, Ramsha Khan, Sarah Amin, Irum Fatima, Yasir Qayyum, (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: Aim of this study was to find iron deficiency anemia and the relationship between people who consumed junk food. Study design: Observational survey base study Method: This study was conducted from March 2022 to May 2022. The data of this study was collected through a questionnaire filled by people of age 18 to 35 years. Consent was attached at the end of the questionnaire that informed the purpose of the data collection and shows the willingness of the participant. The participant who filled out the questionnaire were 200 in number. The data about fast food was gathered using a food frequency checklist that has 25 different fast commonly eaten by people. Body weight and height were used to find the BMI and hemoglobin level was checked using the hematology analyzer at the clinical laboratory of the hospital. The study was approved by the Health Research Ethical Committee of the hospital. Results: Out of 200 participants 50 (25%) were male and 150 (75%) were females. the number of participants having an age greater than 18 years was 136 (68%) and having an age less than 35 years was 64 (32%), most people were educated with a literacy rate of 190 (95%) and 10 (5%) were not educated. Overall anemia awareness was found in 85 (42.5%) people and 115 (57.5%) did not know about anemia. Based on family income, we divided into three groups where the numbers of people from low-income families were 13 (6.5%), the middle class was 40 (20%) and the high income was 140 (73.5%). While checking the hemoglobin level of all we come out with 13(15%) participants with normal hemoglobin levels and 170 (85%) patients were found with anemia having Hb level Anemia<12mg/dL. Out of 170 anemic patients, 20 (11.76%) patients were underweight, 90 (52.94%) patients were of normal weight, 30 (17.65%) were anemic with overweight and 30 (17.65%) were obese. For all measured mean ±, SD = 28.5 ± 2.33. we found a greater number of iron deficiency anemia patients with moderate activity mean ± SD value for physical activity, 54 ±11.76, and fewer people with regular breakfast. Junk food consumption was high in anemic patients 155 (91.17%) and 135 (79.41%) anemic patients with daily junk food consumption. Results of Spearman correlation show mean ± SD was 140 ± 10.11 with a positive correlation of r value 3.05 and significant p-value 0.02. Anemia with 142 ± 9.56 with positive correlation results with r value 1.04 and p-value 0.03. Conclusion: We concluded that a positive correlation shows the direct proportion relationship between junk food and anemia that was higher the consumption of junk food higher the chances of anemia occurrence, lesser the consumption of junk food lower the chances to be anemic. Keywords: Anemia, junk food, iron deficiency